Why literature? : the value of literary reading and what it means for teaching - Bruns, Cristina Vischer (New York : Continuum, 2011)
'Why Literature?' offers a conception of the value of literary reading that demonstrates its importance for psychological and social well-being, and works out the implications of that conception for how we teach literature in universities.
Why read literature? -- From words on paper to an object in transitional space : reading for the formative use of literature -- Recent conceptions of literary education and their potential impact on students' formative use of literature -- Toward a literacy education conducive to the formative use of literature.
Includes bibliographical references (p. [153]-156) and index.
Keywords: Literature -- Study and teaching (Higher) -- United States; Books and reading